Wpływ szkoły na bierność polityczną ludzi młodych w Polsce (Świat Idei i Polityki, 2014)
Young people in Poland are politically passive. Indifference to politics and public affairs comes from the way of socialization of children and adolescents that takes place at school. Polish school is devoid of true self-governance, and dominant social relations in it are not democratie. Students behaviour do not have opportunities to develop civic competence.